2005
DOI: 10.1182/blood-2004-07-2819
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of sexual dimorphism to regulatory T cells: estradiol promotes IFN-γ production by invariant natural killer T cells

Abstract: Mechanisms accounting for gender dimorphism during immune responses are still poorly understood. Since invariant natural killer T (iNKT) cells exert important regulatory functions through their capacity to produce both T helper 1 (Th1) and Th2 cytokines, we addressed the question of whether these activities could be modulated by sexual hormones. We found that in vivo challenge with the specific ligand of iNKT cells, alpha-galactosylceramide (alpha-GalCer), induced significantly higher concentrations of interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…This apparent discrepancy between physiological and supraestrus levels of E 2 was previously reported by our group in other extrareproductive effects, such as atherosclerosis prevention (10) and modulation of invariant natural killer T cells (11).…”
Section: Discussionmentioning
confidence: 59%
“…This apparent discrepancy between physiological and supraestrus levels of E 2 was previously reported by our group in other extrareproductive effects, such as atherosclerosis prevention (10) and modulation of invariant natural killer T cells (11).…”
Section: Discussionmentioning
confidence: 59%
“…The decreased IRF-1 in splenocytes from estrogentreated mice, which were activated with T-cell stimulants, was surprising considering that we and others have shown that estrogen promotes IFN-g, a cytokine that induces IRF-1 (Fox et al 1991, Karpuzoglu-Sahin et al 2001, Maret et al 2003, Gourdy et al 2005, Nakaya et al 2006. The importance of IFN-g in IRF-1 induction is evidenced by the findings that IRF-1 was markedly decreased in Con-A-activated splenocytes from IFN-g K / K mice.…”
Section: Discussionmentioning
confidence: 77%
“…Estrogens are not always immunosuppressive and can exacerbate autoantibody-mediated autoimmune diseases such as lupus-like syndrome [34,35] and experimental autoimmune myasthenia gravis [17]. We and others have documented an enhancing effect of E2 on antigen-specific responses of conventional CD4 1 T cells [16] as well as NKT cells [36], characterized by enhanced production of type-1 cytokines. These pro-inflammatory effects were observed in Ovx mice supplemented with low doses of exogenous E2 and were mediated through ERa signaling in hematopoietic cells [16].…”
Section: Discussionmentioning
confidence: 99%